Bangalore - indijski Silicon valley - Bedrač, Jasmina (Geografski obzornik, 2001)
Bangalore, the capital of Indian state Karnataka is experiencing in the last few years a quick development, which is mainly result of Information Technology Policy that was announced in the year 1997. In spite of this development, Bangalore remains typical Indian city with increasing differences between wealthy and poor people.
Keywords: Bangalore; družbene razmere; Indija; mesta; regionalna geografija; revščina